Bottomline banking : meeting the challenges for survival & success - McCoy, John B.; Frieder, Larry A.; Hedges, Robert B., Jr. (Chicago, Ill. : Probus Pub. Co., 1994)
The three authors in Bottomline Banking lay out the blueprint for transitioning to a new financial services paradigm. The book explores and explains the phenomenon of the superregional banking entity.
Includes bibliographical references and index.
rua 09/11/16
Loans
Keywords: Bank management; Bank mergers; Banks and banking; Bank loans